MANUSIA DAN DIMENSI BIOLOGIS-REPRODUKSINYA DALAM AL-QURAN - Ahmad Mujahid (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2016)
A discussion of the human is one of the themes, which is always interesting to be discussed from different angle of approach. Discussion humans in this paper from the point of view of the Qur'an, which includes a discussion of the terms of what is used in the Koran refers to a human, the human element in the creation of al-Quran and al-Quran views regarding biological-reproductive human dimension.